Discounting Humanity: When Consumers are Price Conscious, Employees Appear Less Human. Issue 2 (9th January 2018) - Henkel, Alexander P.; Boegershausen, Johannes; Hoegg, JoAndrea; Aquino, Karl; Lemmink, Jos
Abstract : Consumers are frequently bombarded with a myriad of marketing tactics. One tactic regularly employed by thrift‐oriented brands is to highlight low prices, discounts, and sales promotions. When consumers encounter these low‐price signals, they may adopt a price conscious mentality, that is, a singular focus on getting the cheapest deal. A price conscious mentality is likely beneficial for consumers, as it helps them save money. However, it is also possible that it has negative implications, particularly for how consumers perceive and interact with other human beings in the marketplace, such as customer service employees. The current research addresses this issue by investigating how consumers' price conscious mentality impacts their perceptions of employees' humanity. Results from four studies demonstrate that a price conscious mentality can lead consumers away from fully recognizing the human qualities of employees. The findings also suggest that this subtle form of dehumanization can result in harsher treatment of employees when they provide less than satisfactory service. Abstract : This article is part of the issue "Marketplace Morality"